The impact of rainfall variability on food security and the sustainability of aquatic ecosystems in Barru Regency, South Sulawesi - Agus Kurniawan B; Awaluddin Awaluddin; Junaedi Junaedi (Jurnal Perikanan Terpadu, 2026)
Rainfall variability is an important factor in food security and the balance of aquatic ecosystems, especially in coastal areas such as Barru Regency, South Sulawesi. This study aims to analyze rainfall trends over the last five years (2019–2023) and evaluate its impact on the agricultural and fisheries sectors. Rainfall data was collected from various observation stations and analyzed using descriptive statistical methods, spatial mapping based on Geographic Information System (GIS), and predictive modeling using Autoregressive Integrated Moving Average (ARIMA) and Machine Learning. The research results show significant fluctuations in rainfall patterns, with the highest increase in rainfall in 2021–2022 and a drastic decrease in 2023. This variability causes an imbalance in water availability, which impacts cropping patterns, agricultural productivity, and the risk of floods and droughts. In the fisheries sector, changes in rainfall contribute to increased sedimentation and fluctuations in salinity in coastal waters, which affect fish habitats and the sustainability of marine ecosystems. Model predictions show that rainfall patterns in Barru Regency follow a two- to three-year cycle, with the possibility of increasing again in 2024–2025. To face this challenge, data-based mitigation strategies are needed, including building water storage infrastructure, implementing adaptive irrigation systems, and strengthening early warning systems based on predictive models. The results of this research contribute to water resource management and food security, as well as supporting climate change adaptation policies in tropical coastal areas.